Protection of Cyberbullying Victims in Indonesia (An Overview of Law and Victimology) (Semarang State University Undergraduate Law and Society Review, 2023)
In some cases when the perpetrator of the crime has been sentenced to criminal sanctions, the condition of the victim of the crime is ignored. The issue of justice and respect for human rights in Indonesia does not only apply to perpetrators of crimes, but also victims of crimes. Law enforcement in this country is often colored with things that are contrary to it. Often in people's lives it shows that both justice and respect for human rights have received less serious attention from the government. Stated in Pancasila, as the philosophy of life of the Indonesian people, the issue of humanity and justice has a very important place for the realization of the 2nd Precept, namely just and civilized humanity and the 5th Precept, namely social justice for all Indonesian people. The government in protecting victims is contained in the law specifically regulating witnesses and victims. Law Number 13 of 2006 concerning the Protection of Witnesses and Victims and followed up with Government Regulation Number 44 of 2008 concerning the Provision of Compensation, Restitution, and Assistance to Witnesses and Victims. For parties, both victims and witnesses who feel they are in a very big threat, their testimonies can also be read out in court and can even give written testimony or online with the approval of the judge. Victims in a crime or crime have a much greater vulnerability in suffering losses both physically and psychologically or materially or immaterially.